HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN KONSUMSI SAYUR DAN BUAH PADA ANAK PRASEKOLAH - Anggreny, Yecy; Niriyah, Sekani (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p03, 2022)
Low levels of vegetable and fruit consumption made preschooler susceptible to disease. This study aimed to find out the relationship of maternal education levels to vegetable and fruit consumption in preschooler. The research method was a type of analytical quantitative research, with a correlation design and a cross-sectional approach. This research was conducted at Payung Sekaki Public Health Center. Sample of this study were 192 mothers who had a preschooler. Sampling techniques used purposive sampling. The data was collected by using questionnaire which was created by researchers and had been tested for validity and reliability before. Data was analyzed by using chi-square test. The results of the bivariate analysis obtained a value of 0,045 (< 0,05) which means there was a significant relationship between maternal education levels and vegetable and fruit consumption. Thus, the public health center was expect to provide education and health information to mothers about how to serve food for preschooler which more interesting and nutritious.